Ethical Literary Criticism, Brain Text, and Ian McEwan's Machines Like Me - Shang, Biwu (Archīum Ateneo, 2024)
From the perspective of the conceptual system of ethical literary criticism and specific key concepts such as brain text and electronic text, this paper attempts to examine the conflicts between the mechanical and the human in Ian McEwan’s novel Machines Like Me (2019) in order to explore issues such as natural selection, ethical selection, ethical consciousness, and artificial intelligence. Taking these thematic concerns as reference points, this paper argues that a human being is a product of natural selection and ethical selection, while a machine is a product of scientific selection. In the novel, the conflicts between the three main characters, Charlie Friend, Miranda, and Adam, largely correspond with the conflicts between ethical selection and scientific selection. On the other hand, the conflict revolving around Adam tackles ethical concerns from a non-human perspective. As a machine, Adam has no biological brain text but only an electronic text used for storing and processing information. He thus has no ethical consciousness to tell good from evil. Arguably, then, the paper contends that artificial intelligence is merely a type of electronic text and as such, cannot replace the text of the human brain, which accounts for Adam’s failure to deal with ethical issues in the human world.